The Impact of Slums on Public Health in the Talang Putri Area of Plaju Sub-District - Putri, Mega Kusuma; Mentari, Mentari; Nuranisa, Nuranisa (Sumatra Journal of Disaster, Geography and Geography Education, 2020)
The purpose of this study was to describe the conditions of the slum settlements and the health of the people living in the area. The method used in this research is a qualitative method with a case study approach. The informants in this study were the people who lived in the slum areas of Talang Putri Village, Palembang City. Determination of informants / respondents using purposive sampling, namely taking informants according to the criteria determined by the researcher. Data collection techniques used were observation, interviews and documentation. Data analysis techniques use data reduction, display data and conclusion drawing / verification. The results of the data analysis show that the slum settlements in the Talang Putri area are due to the lack of awareness of the residents about where they live. In addition, other supporting factors include the low economic situation and the lack of education, which means that almost all residents in Talang Putri attend school only at the elementary level, so that it can affect their knowledge and understanding of the community. The majority of residential building conditions there are wood / planks of 85.5%. And most of the Talang Putri community is accustomed to littering, namely on open land. 68.7% of the Talang Putri community hardly care about the cleanliness of the environment where they live. So that it makes many residents sick, from skin diseases to dengue fever.